The Impact of Reward and Punishment to Increase the Motivation of Teachers and Academic Staff - A Amir; Muthoifin; Mr. Anat Maisu; Alberto Emmanuel Conti Morales; Murtala Hanafi (Walidem Institute and Publishing (WIP), 2023)
The purpose of this study is to analyze the application of reward and punishment as well as spiritual guidance in increasing teacher motivation at SMP Al-Qolam Muhammadiyah Gemolong. The school emphasizes a religious approach to reward and punishment, focusing on the heart and psychological aspects of teachers. The application of reward and punishment is proportionate, focusing on rewarding good behaviour rather than punishing bad behaviour. The school also emphasizes the importance of working for the afterlife, not just for worldly gain. The paper concludes that the application of reward and punishment, as well as spiritual guidance, has resulted in a positive and motivated work environment for teachers at SMP Al-Qolam Muhammadiyah Gemolong and can be applied in other institutions for long-term quality of human resources. Schools must continue to improve their quality and standards.